Biocontrol Mechanism of Bacillus thuringiensis GBAC46 Against Diseases and Pests Caused by Fusarium verticillioides and Spodoptera frugiperda - Zhao Liang; Qurban Ali; Huijun Wu; Qin Gu; Xin Liu; Houjun Sun; Xuewen Gao (Biomolecules)
Bacillus thuringiensis (Bt) is widely recognized as the most important microbial pesticide controlling various insect pests and diseases due to its insecticidal crystal proteins (ICPs) and antimicrobial metabolites. The current study investigates the biocontrol potential of B. thuringiensis GBAC46 against the fungal pathogen Fusarium verticillioides and the insect pest Spodoptera frugiperda through multiple mechanisms. Phenotypic experiments revealed that GBAC46 effectively inhibited F. verticillioides growth by inducing reactive oxygen species (ROS) accumulation and showed enhanced larvicidal activity against second instar S. frugiperda larvae. Pot experiments showed that feeding by S. frugiperda enhanced F. verticillioides infection in maize. The Bt strain GBAC46 effectively controlled both pests and diseases in greenhouse maize seedlings. Applying the Bt strain GBAC46 reduced feeding damage from S. frugiperda, decreased leaf yellowing and wilting caused by F. verticillioides, and improved growth indicators such as plant height, fresh weight, and dry weight. RT-qPCR results revealed that the Bt strain GBAC46 induced key defense genes in maize involved in activating salicylic acid, jasmonic acid, and ethylene pathways. The overall study demonstrated and confirmed the GBAC46 strain as a promising microbial agent for disease and pest management.